Profit Sharing Pattern in Balinese Cattle Fattening Arguments - Astiti, Ni Made Ayu Gemuh Rasa; Surasmi, Ida Ayu; Wodu, Ye Saya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to analyze the pattern of profit sharing in Balinese cattle and the factors that affect it. This study uses survey methods and interviews with Balinese cattle breeders and herders in Bali. The results of the study show that the commonly used profit-sharing patterns are the 50:50, 60:40, and 70:30 patterns for female cattle, which are rumoured through the Simantri pattern. Factors that affect the profit-sharing pattern are production costs, risks faced by each party, contributions made by each party, and the selling price of cattle. The study also demonstrates that a fair and transparent profit-sharing arrangement can enhance trust and cooperation between farmers and herders. The results of this study are expected to serve as a reference for farmers, herders, and policymakers in developing a more effective and efficient Balinese cattle farming business. Contribution to Sustainable Development Goals (SDGs):SDG 1: No Poverty SDG 2: Zero Hunger SDG 8: Decent Work and Economic Growth SDG 12: Responsible Consumption and Production SDG 17: Partnerships for the Goals